Parecoxib reduces renal injury in an ischemia/reperfusion model in rats - Calistro Neto,José Pedro (2015)
PURPOSE: To evaluate the effect of parecoxib (an NSAID) on renal function by measuring plasma NGAL (serum neutrophil gelatinase-associated lipocalin) levels in an induced-ischemia rat model.METHODS: Forty male Wistar rats were randomly assigned to one of four groups: Ischemia (I), Ischemia/parecoxib (IP), No-ischemia (NI), and No-ischemia/parecoxib (NIP). Body weight, mean arterial pressure, heart rate, body temperature, NGAL levels, and renal histology were compared across groups.RESULTS: The Ischemia (I) group, which did not receive parecoxib, showed the highest NGAL levels (p=0.001), while the IP group, which received the medication, had NGAL levels similar to those of the non-ischemic (NI and NIP) groups.CONCLUSION:Parecoxib resulted in renal protection in this experimental model.